2011
DOI: 10.3389/fneur.2011.00059
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic amygdalar transplants in adult rats with motor cortex lesions: a molecular and electrophysiological analysis

Abstract: Transplants of embryonic nervous tissue ameliorate motor deficits induced by motor cortex lesions in adult animals. Restoration of lost brain functions has been recently shown in grafts of homotopic cortical origin, to be associated with a functional integration of the transplant after development of reciprocal host–graft connections. Nevertheless little is known about physiological properties or gene expression profiles of cortical implants with functional restorative capacity but no cortical origin. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
0
3
0
3
Order By: Relevance
“…For relative mRNA quantification C q values (C q , standard name for threshold cycle or crossing point value according to the Real-Time PCR Data Markup Language, RDML guidelines, [ 36 ]) were calculated in each sample set for reference and target genes. The expression of each target gene relative to a normalizing factor (a reference gene that was chosen accordingly to its stability; see section below) was calculated using the 2 −ΔCq method [ 37 , 38 ] as described by the manufacturer (Applied Biosystems: User Bulletin 2). Changes in gene expression through the time course were reported as percent changes relative to basal control expression at time zero (t = 0 min, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…For relative mRNA quantification C q values (C q , standard name for threshold cycle or crossing point value according to the Real-Time PCR Data Markup Language, RDML guidelines, [ 36 ]) were calculated in each sample set for reference and target genes. The expression of each target gene relative to a normalizing factor (a reference gene that was chosen accordingly to its stability; see section below) was calculated using the 2 −ΔCq method [ 37 , 38 ] as described by the manufacturer (Applied Biosystems: User Bulletin 2). Changes in gene expression through the time course were reported as percent changes relative to basal control expression at time zero (t = 0 min, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…These studies have achieved remarkable results in showing that grafted neurons can successfully survive and synaptic connections can be established between the host and donor cells 1 2 3 . Importantly, grafted neurons are electrophysiologically active in responding to adjacent host cortex 4 5 6 , and the lost functions can be partially recovered after transplantation 7 8 9 .…”
mentioning
confidence: 99%
“…In the past few years, the survival capacity of embryonic neurons transplanted in different regions of the adult brain has been demonstrated, and many studies have reported their repair potential at the neuroanatomical and functional levels (Lindvall et al, 1990 ; Plumet et al, 1993 ; Ebrahimi-Gaillard et al, 1995 ; Gaillard et al, 2007 , 2009 ; Santos-Torres et al, 2009 ; Thompson et al, 2009 ; Jiménez-Díaz et al, 2011 ; Lu et al, 2012 ; Klein et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%